The Applied Strategies for the Translation in ’Prajatantra ra Yuwajagat’ - Saud, Krishna Singh (Journal of Jayaprithvi Multiple Campus, 2025)
This paper studies the applied strategies in translation while translating a text from source language to target language. The main purpose of the study is to collect data related to applied strategies, and analyze and interpret them for the conclusion. The data is collected from all the sixty-one sentences of five paragraphs and both Nepali and English version of the essay ’Prajatantra ra Yuwajagat’ and ’Democracy and the Youth’ respectively. The qualitative technique is used to analyze and interpret the data derived from the study. It is found that the translator has used the aspects like linguistic, cultural and pragmatic as well as the strategies such as literal translation, equivalence, substitution, omission, addition and chunking. It is further observed that the translator has tried to translate by preserving the originality of the text as well as the flow and logical order. It is recommended that the use of strategies should be examined in other translations by the writer for further results.